Nitrogen-Doped Carbon Foams Synthesized from Banana Peel and Zinc Complex Template for Adsorption of CO2, CH4, and N2 - Arami-Niya, Arash; Rufford, T.E.; Zhu, Z. (AMER CHEMICAL SOC, 2016)
We report nitrogen-doped, activated carbon foams prepared from banana peels using a self-template method with zinc nitrate, 2-aminophenol, and furfural involved. Importantly, we have extended the banana peel zinc complex soft-template method to investigate the effects of carbonization temperature and postcarbonization CO2 activation on the carbon pore structure, and examined the effect of N-content on the carbon foam's equilibrium adsorption capacity for CO2. The carbon foams contain up to 6.0 wt % nitrogen and feature cellular macroporous structures with BET specific surface areas up to 1426 m2·g-1. The potential of the carbon foams for CO2/N2, CO2/CH4, and CH4/N2 separations was evaluated by measurement of pure fluid adsorption capacities using a gravimetric adsorption apparatus and calculation of adsorption selectivies at a range of conditions using ideal adsorption solution theory (IAST). The adsorption capacities at a 4000 kPa and 298 K were CO2 9.21 mmol·g-1, CH4 5.29 mmol·g-1, and N2 3.29 mmol·g-1.